Investment and the golden rule in the European Union - Ada Cristina Marinescu (Financial Studies, 2018)
We will study in this paper the relation between public investment, public debt and fiscal rules in the European Union countries. The strict fiscal rules imposed by EU have negatively affected the investments. The decline in public investment in European Union is related to the fiscal rules (mainly the deficit rule) included in the Stability and Growth Pact (SGP). There have been made several attempts to amend the SGP in such a way to grant a more flexible treatment to capital expenditure when fixing budgetary targets and ceilings. According to the golden rule of budget deficit, investments can be financed through loans, while current expenditure should be financed from taxes. The golden rule promotes thus intergenerational fairness and contributes to economic growth.
Keywords: E62; H60; E60; 330; fiscal rules; public debt; public deficit; Stability and Growth Pact